Pengaruh Imbangan Pennisetum purpureum cv.Mott dan Indigofera zolligeriana dalam Ransum terhadap Total VFA, NH3 dan Populasi Protozoa Rumen in vitro. - Siti Wulandari Barokah; irma badarina; Dwatmadji Dwatmadji (Fakultas Peternakan Universitas Tulang Bawang Lampung, 2022)
This study aims to evaluate the level of Indigofera zollingeriana with Pennisetum purpureum cv. Mott Â in ration on rumen fermentation characteristics (total VFA, NH3 and protozoa population) in vitro. The study used a completely randomized design (CRD), consisting of 5 treatments and 4 replications. P1 = 60% Pennisetum purpureum cv. Mott, P2 = 45% Pennisetum purpureum cv. Mott + 15% Indigofera zollingeriana, P3 = 30% Pennisetum purpureum cv. Mott + 30% Indigofera zollingeriana, P4 = 15% Pennisetum purpureum cv. Mott + 45% Indigofera zollingeriana, P5 = 60% Indigofera zollingeriana. All treatments received an additional 40% fine ricebran. The results showed that the level of Indigofera zollingeriana flour with Pennisetum purpureum cv. Mott had no significant effect on total VFA and NH3.Â Total VFA and NH3 ranged from 131.65 mM-143.24 mM and 12.61 mM-13.74 mM, respectively. Meanwhile, the population of protozoa had a significant effect (P<0.05). DMRT further test results showed that P3 was significantly Â (P<0.05) lower than P1, P2, P4 and P5. The average population of the protozoa ranged from 53.125 cells/ml to 90,625 cells/ml. Based on the results of the study, it can be concluded that the administration of Indigofera zollingeriana leaves by 30% was able to reduce the protozoan population in the rumen of FH cattle but had no significant effect on total VFA production and ammonia (NH3) concentration. Keywords: Rumen Fermentation Characteristics, Indigofera zollingeriana, In Vitro